The Effect of Futsal on the Cardiovascular Endurance of Students at SMAN 1 Kota Bengkulu - Muhamad Rizki Ramadani; Egy Juliansyah; Lintaradi Saputra; Bunga Dwi Ginanti; Yoga Ramadhan; Ajis Sumantri (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to examine the effect of futsal on the cardiovascular endurance of students at SMAN 1 Kota Bengkulu. Futsal was selected as the research subject because it is an intense physical activity involving comprehensive body movements that can enhance heart and lung capacity. This study employed a comparative design with a sample of 25 students divided into two groups: a group participating in routine futsal training and a control group not involved in futsal activities. Cardiovascular endurance was measured using the VO2 Max test before and after a 6-week futsal training period. The results of the analysis showed a significant difference in the improvement of cardiovascular endurance between the futsal group and the control group. These findings provide an important contribution to the development of sports programs that support the enhancement of cardiovascular and respiratory health in students.